Differential gender bias in self-predicted performance in medical tests - Adrian Soto-Mota; Andrés Castañeda Prado; María Fernanda González Lara; Laura Jael Ortiz; Pablo Soto-Mota (BMC Medical Education)
Abstract Background The proportions of men and women in some residency programs have been unbalanced. In recent years, Mexican regulations surrounding the national standardized test for residency programs (ENARM) have changed, allowing applicants to choose their desired residency program after knowing their score (instead of before taking the exam). Since, on average, women are more risk-averse than men, we hypothesized that the new regulation may have influenced the proportion of women applying to competitive residency programs by letting them choose without the uncertainty of their future test performance. Additionally, we evaluated if the accuracy in predicting test performance differs between men and women studying Medicine. Methods We analyzed data from 452,079 medical residency applications (and their respective ENARM performance) between 2010 and 2022. Additionally, we evaluated self-predicted test performance accuracy in 266 students (of which 61.7% were medical students), which differed between men and students of different biomedical faculties (Nutrition, Psychology, and Biosciences). As part of our sensitivity analyses, we examined whether the perceived difficulty of the evaluated topic or its relevance to their future career plans affected their predictions and test performance. Results The proportion of women in highly competitive residency programs significantly increased during the years when applicants chose their programs after seeing their scores. While both Men and Women studying Medicine were more competitive and scored higher than students in other Biomedical faculties, Men studying Medicine predicted higher test scores than their female counterparts despite their actual scores not being statistically different. In comparison with women, men had larger overestimation errors about their actual test performance, predicted they would rank higher than their class peers, and predicted higher test scores independently of how difficult they perceived the tested topic to be. Conclusion The percentage of women in highly competitive programs increased significantly when applicants chose their program after knowing their standardized test scores. Men studying Medicine overestimated their test performance vs. all other groups. Although their actual scores were not statistically different from those of women, men predicted higher test scores regardless of how difficult they perceived the evaluated topic to be or how relevant they thought it would be for their future career plans.